Perlindungan Hukum Bagi Investor Terhadap Insider Trading di Pasar Modal Dalam Perspektif Undang-Undang Pasar Modal - Ali Murtadho, Nazhif (Magister Kenotariatan, Universitas Jambi, 2024)
This study discusses legal protection for investors against insider trading practices in the capital market based on Law Number 8 of 1995. Insider trading is an illegal action in which individuals use confidential information that is not yet publicly available in securities transactions. This research uses normative legal research or literature law research that focuses on analyzing the norms contained in laws and regulations as well as norms governing the capital market and insider trading aspects in it. The law provides for prohibitions and sanctions against insider trading actors, including the imposition of administrative, criminal, and civil sanctions. However, there are challenges in proving insider trading cases and legal loopholes that can be exploited by perpetrators. Firm and effective law enforcement against insider trading is important to maintain fairness and stability of the capital market and provide legal certainty for investors. This study identifies efforts that can be made to strengthen legal protection for investors and provides recommendations to improve the effectiveness of law enforcement against insider trading in the capital market.